Ethnomedicinal Wisdom of the Kani Tribes in Agasthiayamalai Biosphere Reserve in South India - A. John, De Britto; R, Mahesh; N, Nirmal Kumar (Malaysian Journal of Science, 2008)
This research article deals with ethno botanical exploration and the analysis of folk medicinal uses of five Kani tribal settlements of Tirunelveli District, Tamilnadu. The field survey was carried out in 2006 and 2007. In total, more than 400 plants species are used by the Kani tribes and out of which only 70 species are mentioned here. The present population has little knowledge about the medicinal plants of the area because most of the knowledgeable, older persons have passed away and the younger ones are not informed of traditional methods. However, as in the past, some empirical knowledge of medicinal plants among the tribes continues to be developed and transmitted orally from one generation to the next. All the information were collected and documented in a database using Visual Basic 6.0 and MS Access.